जाति, वर्ग ते सत्ताः तंजौर दे इक ग्रांऽ च दरजेबंदी दे बदलोंदे रूप - Andre Beteille (My University, 2020)
An intensive study of the changing patterns of social stratification in a multi-caste village, Sripuram village in South India. The clarity of the descriptive analysis of the three caste groups and agrarian classes as well as the interactions between them is the main strength of the book.
Dogri translation of Caste, Class and Power: Changing Patterns of Stratification in a Tanjore Village
Keywords: Dogri